Multimodal Radiological Imaging Findings in Premature Infant with Cytomegalovirus and Toxoplasma Coinfection - Johannes Tanaka; Anandhika Dwijaya; Fitri Arianty Lubis (Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Congenital co-infection with Cytomegalovirus (CMV) and Toxoplasma gondii is an extremely rare condition, particularly in premature infants, with overlapping clinical and radiological manifestations involving the central nervous system and respiratory tract. Premature infants are at high risk for intraventricular hemorrhage (IVH), which may be exacerbated by inflammation and impaired vascular maturation related to TORCH infections. Case illustration: A 35-week premature neonate weighing 2100 grams was admitted to the Neonatal Intensive Care Unit (NICU) due to respiratory distress and decreased activity. Serological testing confirmed congenital CMV and Toxoplasma gondii co-infection. Initial postnatal cranial ultrasonography revealed grade II IVH that had not been detected on prenatal ultrasound. Serial radiological follow-up demonstrated progression of IVH to post-hemorrhagic hydrocephalus. Non-contrast cranial computed tomography showed bilateral ventriculomegaly with periventricular calcifications consistent with congenital CMV infection. During hospitalization, serial chest radiographs demonstrated pneumonia with progressive atelectasis. Discussion: This case highlights the importance of a multimodal radiological approach in mapping disease progression in premature infants with TORCH co-infection. Cranial ultrasonography serves as the primary and serial modality for IVH detection, while cranial CT provides confirmation of structural complications, and chest radiography allows monitoring of respiratory involvement. Conclusion: Congenital CMV and Toxoplasma gondii co-infection in premature infants requires heightened vigilance for neurological and respiratory complications. Longitudinal multimodal radiological evaluation plays a pivotal role in disease assessment, clinical decision-making, and early multidisciplinary management.